DEFENDING ART AND POETRY: EMILIO ADOLFO WESTPHALEN IN DIALOGUE WITH TEXTS OF CONTEMPORARY CRITICISM AND POETICS - Flores Alemán, Marco Antonio (2018)
This article aims to put into dialogue Emilio Adolfo Westphalen ideas with contemporary poetry, in order to better positioning Westphalen thinking inside Peruvian and world literature of the late twentieth century. I aim to achieve this by making a contrast between Westphalen poetic and a variety of some other contemporary authors, such as Joao Cabral de Melo Neto, Francis Ponge, Jacques Roubaud, Miguel Casado and Andrés Sánchez Robayna. In the case of Westphalen, I have worked with essays prevenient from La poesía los poemas los poetas, published in 1995, and some other essays from different times and places. The present corpus allows us to look widely Westphalian poetic and leads us to set the discussion about the defense of the Arts and poetry in different contexts of the twentieth century.